Combined Training Improves Executive Functions Without Changing Brain-Derived Neurotrophic Factor Levels of Middle-Aged and Older Adults with Type 2 Diabetes - Silveira-Rodrigues, João Gabriel; Gardênia de Holanda Marinho Nogueira, Nathálya; Faria, Larissa Oliveira; Pereira, Daniele Sirineu; Soares, Danusa Dias (Experimental and Clinical Endocrinology & Diabetes, 2023)
Background Type 2 diabetes mellitus (T2DM) provokes executive function and long-term memory decrements, and aerobic plus resistance training (combined training) may alleviate this T2DM-related cognitive impairment. Brain-derived neurotrophic factor (BDNF) levels have been found to be related to cognitive performance.Aim To analyze the effects of 8-week combined training on executive functions and circulating BDNF levels of subjects with T2DM and verify the association between BDNF levels and combined training-induced changes in executive functions and long-term memory.Methods Thirty-five (63±8 years old) subjects of both sexes were allocated to combined training (n=17, thrice weekly for 8 weeks) or the control group (n=18). Executive functions (evaluated through Trail making test, Stroop color task, and Digit Span), long-term memory (evaluated through the Taylor Complex Figure Test simplified), and plasma samples were compared pre- and post-intervention.Results Combined training improved executive function z-score compared to control (d=1.31). Otherwise, BDNF levels were not statistically altered (combined training group: 179±88 pg/mL vs. 148±108 pg/mL; control group: 163±71 pg/mL vs. 141±84 pg/mL, p>0.05). However, pre-training BDNF levels explained 50.4% of the longitudinal improvements in composite executive function z-score (r=0.71, p<0.01), 33.6% of inhibitory control (r=0.58; p=0.02), and 31.4% of cognitive flexibility (r=0.56, p=0.04) in the combined training group.Conclusion Combined training improved executive functions independently of alterations in resting BDNF levels after 8 weeks. Furthermore, pre-training BDNF levels explained one-half of the variance in combined training-induced improvements in executive functions.
Keywords: physical exercise; cognitive performance; inhibitory control; cognitive flexibility; memory